Accessibility Long Term Perspectives - Kay Axhausen (Journal of Transport and Land Use)
Improved accessibility and its correlate lower generalized cost of contact, travel and transport have been sought by dynamic human societies for their economic and social benefits through- out recorded history. The paper will reflect about this process at a number of different spatial and temporal scales based on a conceptual model. Looking back at European history, it will trace the interaction between Christaller’s logic of local market areas and the idea of (low contact cost) network cities. Focusing on Switzerland since 1950 it will show how network investment changed the relative distribution of population and employment and how this in- teracted with changes in the preferences of the travelers. Using a recent snapshot of how a substantial sample of Swiss maintain their social networks over often very large areas, it will try to answer the question of what will happen in the future, if the current trend of ever lower costs of contact will persist.